Mad honey : a novel [compact disc, unabridged] - Picoult, Jodi, 1966-; Boylan, Jennifer Finney, 1958- (Good morning America book club., 2022)
Olivia McAfee left her husband and moved with her son, Asher, to a small town. When tragedy occurs and Asher becomes a suspect, Olivia must face whether he is revealing the same dark side as his father.